2022
DOI: 10.1007/s12072-022-10330-x
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin improves transplant-free survival after TIPS implantation in patients with refractory ascites: a retrospective multicentre cohort study

Abstract: Background and aims Transjugular intrahepatic portosystemic shunt (TIPS) implantation is an established procedure to treat portal hypertension. Impact of administration of aspirin on transplant-free survival after TIPS remains unknown. Methods A multicenter retrospective analysis including patients with TIPS implantation between 2011 and 2018 at three tertiary German Liver Centers was performed. N = 583 patients were included. Survival analysis was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The decision for anticoagulation further depends on the underlying disease, with BCS or PVT certainly requiring anticoagulation [23]. A recent retrospective multicenter study showed a potential survival benefit for acetylsalicylic acid after TIPS in adults [24], although this opinion is not without detractors [25]. In children, there is no consensus, and the primary indication for TIPS may guide anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…The decision for anticoagulation further depends on the underlying disease, with BCS or PVT certainly requiring anticoagulation [23]. A recent retrospective multicenter study showed a potential survival benefit for acetylsalicylic acid after TIPS in adults [24], although this opinion is not without detractors [25]. In children, there is no consensus, and the primary indication for TIPS may guide anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…The necessity of anticoagulation or antiplatelet therapy after TIPS procedure remains controversial. There are studies which could demonstrate a beneficial effect of the administration of aspirin in terms of post-TIPS survival [59]. Nevertheless, with the occurrence of polytetrafluoroethylene (PTFE)-covered stents, the general rate of shunt dysfunction was observed to be lower [60, 61].…”
Section: Indications and Practical Managementmentioning
confidence: 99%
“…We would like to thank Dr. Wang, Dr. Qi and their team for their interest and appreciate the raised issues regarding our study entitled ‘Aspirin improves transplant-free survival after TIPS implantation in patients with refractory ascites—a retrospective multicenter cohort study’ [ 1 ].…”
Section: To the Editormentioning
confidence: 99%